2022
DOI: 10.3390/ijerph19042346
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Urdu Translation of Berg Balance Scale in People with Parkinson’s Disease

Abstract: Background: The most common assessment tool used in clinical settings to detect changes in balance performance is the Berg Balance Scale (BBS). Thus, the purpose of this study was to translate the BBS into Urdu and investigate the psychometric properties (acceptability, internal consistency reliability, interrater reliability, construct validity) for individuals with Parkinson’s disease (PD). Methods: Eighty patients of either gender with idiopathic Parkinson’s disease, stages I–III on the modified Hoehn–Yahr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…A number of neurological disorders, including PD, are associated with balance impairments. [65] The findings of recent review are in line with the previous SRs on Stroke and Alzheimer’s disease, [66,67] proposing that conventional physiotherapy intervention is inferior to VR technology in improving balance and other subject impairments. Several studies trained patients by using somatosensory game software, and a few studies used traditional exercises as a basis for VR technology application.…”
Section: Discussionsupporting
confidence: 67%
“…A number of neurological disorders, including PD, are associated with balance impairments. [65] The findings of recent review are in line with the previous SRs on Stroke and Alzheimer’s disease, [66,67] proposing that conventional physiotherapy intervention is inferior to VR technology in improving balance and other subject impairments. Several studies trained patients by using somatosensory game software, and a few studies used traditional exercises as a basis for VR technology application.…”
Section: Discussionsupporting
confidence: 67%
“…A number of characteristics contribute to the feasibility of implementing the most widely recommended tools (i.e., BBS, 6MWT, TUG, or 10mWT): they have been highly recommended for use in multiple settings across the care continuum ( 103 ), they are free to use, easy to score, administration time is less than 15 min, and the tools do not require specialized training or equipment ( 104 ). In addition, versions of the BBS are available in many languages (e.g., Brazilian-Portuguese ( 105 ), English ( 106 ), German ( 107 ), Japanese ( 108 ), Norwegian ( 109 ), Persian ( 110 ), Spanish ( 111 ), Turkish ( 112 ), and Urdu ( 113 )). Despite the availability of stroke-specific protocols for administering the 10mWT and 6MWT ( 114 ), there are challenges with their implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…downs et al [37] conducted research to study the BBS and reported that this tool was widely accepted and commonly used because it required less equipment and a shorter duration than other options. in addition, in 2022, Kashif et al [38] demonstrated that the Urdu version of the BBS is a reliable and valid tool with excellent psychometric properties for assessing balance in patients with Parkinson's disease. The BBS has a high relative reliability with an inter-rater reliability of approximately 0.97 (95% Ci 0.96-0.98) and an intra-rater reliability of 0.98 (95% Ci 0.97-0.99) and is generally recognised and frequently used, requiring less equipment and a short period of time [39,40].…”
Section: Discussionmentioning
confidence: 99%